Sone Ki Chidiya - Shaheed Latif; Ismat Chughtai; Moser Baer (New Delhi, India) (New Delhi : Moser Baer Entertainment, 2010)
Lakshmi is a poor girl with a large family to support. She strikes it big time when she gets a chance to star in a film. She falls in love with her flamboyant co-star, Amar. Disillusionment faces her when she learns that he, too is only interested in her wealth. She runs away and tries to commit suicide when she is stopped by a poor writer, Shrikant, who befriends her. It is then that she realizes that not everyone in the world is interested in her purely for her money.
Copyright notice on container: Moser baer
Originally released theatrically in 1958
Summary taken from IMDB.com.
Talat Mahmood, Balraj Sahni and Nutan
NTSC all region
In Hindi. with English Subtitles
Keywords: Family -- Drama; Musical -- Drama